If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1(3y + 4) = 2 Reorder the terms: 12 + -1(4 + 3y) = 2 12 + (4 * -1 + 3y * -1) = 2 12 + (-4 + -3y) = 2 Combine like terms: 12 + -4 = 8 8 + -3y = 2 Solving 8 + -3y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3y = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -3y = 2 + -8 -3y = 2 + -8 Combine like terms: 2 + -8 = -6 -3y = -6 Divide each side by '-3'. y = 2 Simplifying y = 2
| k-12=1+4k-4 | | -6=3(5v-2) | | 7x+xi-3yi=3yi+9i | | 1/5y+6=-17 | | 7x^2y^2-21x^2y^3= | | -3+7x=1+3x | | (2ab)5= | | x/7-9=13/14 | | -5h=-6h-4 | | 54a^4-288a^2+384= | | (2x+3)+(3x+6)= | | 7x-42=42 | | 139.95=23+7x | | (3x+2)+(4x+5)= | | -8x+6x=4 | | 4x^2+72=6x^2 | | 2x-1+7=15 | | 0.4x-0.3=0.7x+1 | | 3x+14=3x-1 | | 7x=19+6y | | -4x+6=12-26 | | 978.3+20= | | 139.95=90+15d | | (3x+5)+(4x+7)= | | 3ab^2+7a^2b= | | -10=6x-6x | | c=90+15d | | -3x+4=5x+8 | | 7x(x+1)=9x-5 | | 5x(z+4)+(z+4)= | | 3t^2+7t+3=0 | | f(x)=4x^2-x-5 |